GROUP-BASED EXERCISE AND COGNITIVE-BEHAVIORAL SKILLS TRAINING FOR OLDER ADULTS WITH OSTEOARTHRITIS. (11th November 2018) - Patel, K V; Adams, L M; Phelan, E A; Turk, D C
Abstract: Older adults with knee osteoarthritis (OA) often restrict physical activity to cope with their pain, increasing risk for mobility disability. We pilot-tested a combination of group-based cognitive-behavioral skills training (CBST; 12, 1-hour classes) and community-based exercise (Enhance Fitness [EF]; 1-hour classes, 3 days/week of balance, endurance, and strength training for 4 months). Eighteen adults age ≥65 years with painful knee OA were randomized 2:1 to either CBST+EF or an active control condition of health education (HE) and EF. Class attendance rates and treatment satisfaction ratings were high and similar between treatment groups. The CBST+EF group had large, clinically significant improvements (pre-post treatment change) in pain, physical performance, and accelerometer-measured physical activity (P-values <0.05), while the control group (HE+EF) had minimal-to-moderate improvements in outcomes. Exit interviews indicated that participants valued and benefitted from the combination of CBST with EF, particularly the pain coping skills training and pedometer-based step monitoring and goal-setting.